Gasto público en salud en Ecuador: ¿cumplimos con los compromisos internacionales? (Tema Central) - Guarderas, Mauricio David (2021)
This descriptive study seeks to verify whether public spending on the health budget in the period 2008-2014 was directed to compliance with the provisions of supranational regulatory frameworks that seek to guarantee health care as a human right. Based on the analysis of that period’s expenditure items, the methodology included a categorization of each item of expenditure, based on the objective set in each of the financed projects, and its classification in the different health dimensions provided by the supranational regulative instruments to which Ecuador is a signatory. Based on this categorization and analysis, it was concluded that 95 % of all resources could be classified in any of the dimensions provided for international instruments and the remaining 5 % did not correspond to any category, which would mean that approximately 584 million dollars were destined to other different purposes; ceasing to be focused on strengthening Ecuador’s public health system that allows it to guarantee the Ecuadorian’s right to health.